Detecting the Effects of Sustained Glacier Wastage on Streamflow in Variably Glacierized Catchments - Moore, R. D.; Pelto, Ben; Menounos, Brian; Hutchinson, David (Frontiers in Earth Science, 2020)
This study focused on the effects of glacier wastage on streamflow in the Canadian portion of the Columbia River headwaters over the period 1977 to 2017. Between 1985 and 2013, glacier coverage decreased by up to 2% of catchment area for the 35 study catchments. The mean wastage flux contribution to streamflow had a positive relation with fractional glacier coverage and an inverse relation with catchment water yield. Glacier mass change estimates suggest that wastage flux contributions declined between 1985-1999 and 2000-2018, but the estimates are subject to substantial uncertainty. Annual wastage flux contributions over a four-year period for two study catchments ranged from 8 to 13% of annual water yield for a catchment with 17% glacier cover, with glaciers extending below treeline, and 9 to 19% for a smaller alpine catchment with 57% glacier cover. After accounting statistically for climatic forcing and non-glacial contributions to streamflow, August runoff from glacierized catchments decreased through time at a rate that was linearly related to loss of glacier cover. The analyses suggest that glacier-melt contributions to August runoff have already have passed peak water, and that these reductions have exacerbated a regional climate-driven trend to decreased August streamflow contributions from unglacierized areas.